Is It Possible to Achieve Favorable Accelerated Dental Changes with No Periodontal Complications When Retracting Upper Anterior Teeth Assisted by Flapless Corticotomy Compared to Traditional Corticotomy? A Two-Arm Randomized Controlled Trial - Hanin Nizar Khlef; Mohammad Younis Hajeer (The Scientific World Journal)
Objectives. The objective of this trial was to evaluate the dental changes, periodontal health, and tooth vitality in mini-screw-supported en-masse retraction with two corticotomy-based acceleration techniques. Study Design. The sample included 38 adult patients presenting with class II division 1 malocclusion (three males, 35 females; age range between 18 and 30 years), needing the extraction of upper first premolars followed by en-masse retraction. The sample was divided randomly and equally into two groups. Randomization was carried out by random numbers generated by the computer with a 1 : 1 allocation ratio. The allocation concealment was carried out by sequentially numbered, opaque, sealed envelopes. The interventions were traditional corticotomy (TC) versus flapless corticotomy (FC). Mini-screws were inserted between the upper second premolar and first molar, bilaterally. The primary outcome was evaluating dental changes. Secondary outcomes were the periodontal health and pulp vitality of the maxillary teeth. Mann–Whitney U test and two-sample t-test with Bonferroni correction were used to analyze the data. Results. The en-masse retraction rate in the first three months was higher in the TC group than the FC group (1.82, 1.66, and 1.39 mm/month vs 1.60, 1.42, and 1.22 mm/month, respectively) with statistically significant differences (P<0.001, P<0.001, P=0.001, respectively). The en-masse retraction amount was greater in the TC group than the FC group (6.84 mm vs 6.18 mm, respectively) with statistically significant differences (P=0.002). There was an increase in the inter-canine and inter-molar widths with a minor distal movement of the upper first molar in the two groups, with no significant differences between them (P>0.008). The values of gingival, papillary bleeding and plaque indices in the TC group were significantly greater than those in the FC group after performing the corticotomy (P<0.001, P<0.003, P=0.002, respectively). No gingival recession was found on any of the examined teeth in both groups. All teeth maintained their vitality at all measurement times in both groups. No severe harms were noticed in any group. Conclusions. Both traditional and flapless corticotomy techniques resulted in clinically similar rates of the en-masse retraction of upper anterior teeth, with similar dental changes and no significant periodontal complications or tooth vitality loss. The minimally invasive flapless corticotomy appeared to be a good alternative to the more invasive traditional corticotomy. This trial is registered with https://www.clinicaltrials.gov (Identification code: NCT04847492), retrospectively registered.